Brain metastasis cell lines panel: a public resource of organotropic cell lines - Valiente, Manuel; Swearingen, Amanda E. D. Van; Anders, Carey K.; Bairoch, Amos; Boire, Adrienne; Bos, Paula D.; Cittelly, Diana M.; Erez, Neta; Ferraro, Gino B.; Fukumura, Dai; Gril, Brunilde; Herlyn, Meenhard; et al. (Cancer research, 2020)
Spread of cancer to the brain remains an unmet clinical need in spite of the increasing number of cases among patients with lung, breast cancer, and melanoma most notably. Although research on brain metastasis was considered a minor aspect in the past due to its untreatable nature and invariable lethality, nowadays, limited but encouraging examples have questioned this statement, making it more attractive for basic and clinical researchers. Evidences of its own biological identity (i.e., specific microenvironment) and particular therapeutic requirements (i.e., presence of blood-brain barrier, blood-tumor barrier, molecular differences with the primary tumor) are thought to be critical aspects that must be functionally exploited using preclinical models. We present the coordinated effort of 19 laboratories to compile comprehensive information related to brain metastasis experimental models. Each laboratory has provided details on the cancer cell lines they have generated or characterized as being capable of forming metastatic colonies in the brain, as well as principle methodologies of brain metastasis research. The Brain Metastasis Cell Lines Panel (BrMPanel) represents the first of its class and includes information about the cell line, how tropism to the brain was established, and the behavior of each model in vivo. These and other aspects described are intended to assist investigators in choosing the most suitable cell line for research on brain metastasis. The main goal of this effort is to facilitate research on this unmet clinical need, to improve models through a collaborative environment, and to promote the exchange of information on these valuable resources.
Gesehen am 14.12.2020